Study on outcome of guided newborn care in postnatal ward and common practices of newborn care among mothers followed in outpatient department at Hi-Tech medical college and hospital, Bhubaneswar - Sabat, Maneesha; Swain, Suryakanta; Agrawal, Hemant; Panda, Aishwarya; Beura, Sthita Prajnya; Panda, Rakesh (International Journal of Contemporary Pediatrics, 2021)
Background: Neonatal period is the most vulnerable phase in a child's life. The aim and goal of newborn care is not only to reduce neonatal mortality but more importantly to ensure their survival to the fullest. The neonatal mortality rate of India is 22 per 1000 live births. The neonatal period is only for 28 days yet it accounts for significant deaths under 5 years of age. Newborn morbidity and mortality contribute significantly to the infant mortality and under-five mortality rates in developing countries. About two-thirds of all infant deaths and 38% of all under-five deaths occur during the neonatal period, resulting in about 4 million neonatal deaths globally per year. Infant and under-five mortality ratio in developing countries have declined significantly in the past couple of decades, yet neonatal mortality rates have remained relatively static. The objective of this study was to understand the outcome of guided newborn care along with the patterns and determinants of essential newborn care and practices. Methods: A prospective cohort study was done among new borns in the postnatal ward and the outpatient (OPD) based new borns at HMCH Bhubaneswar from July 2020 to June 2021. The mothers in the postnatal ward were taught cord care, skin care, optimal thermal care and neonatal feeding practices. The regular follow-up was done maximum up to 7 days. New born who came to OPD were evaluated on perspective of essential new born care and practices, followed by their mothers at home. A questionnaire was formulated for the OPD based patients to be answered before and after guidance. Results: 100 early neonates were taken (N=50 from postnatal ward and N=50 from OPD). Out of 50 neonates in the postnatal ward. 4 (8%) had abdominal colic, 10 (20%) had skin rashes, 2 (4%) had fever, 5 (10%) had feeding issues and 9 (18%) had neonatal hyperbilirubinemia respectively. In OPD neonates 3 (6%) were diagnosed with early onset neonatal sepsis (EONS), 7 (14%) had refusal to feed, 12 (24%) had skin rashes, 5 (10%) had abdominal colic, 14 (28%) were applying coconut oil and 7 (14%) developed hyperbilirubinemia. Whereas in OPD 5 (10%) neonates needed admission NICU and rest were managed symptomatically. Conclusions: New born care education and guidance helped in reduction of EONS, in gaining appropriate weight, in delivering optimal thermal care, practicing healthy skin care and implementing proper feeding techniques. All mothers need proper counselling and guidance in essential new born care.